Strategic Information Systems Planning Analysis Using the Ward and Peppard Method: A Case Study - Ardiansyah, Muhammad; Wahyudi, Angga (Journal of Information System and Informatics, 2024)
This paper aims to develop a strategic information systems (IS) plan using the Ward and Peppard methodology, employing a qualitative approach with data collected through direct observations, interviews with key stakeholders, and a comprehensive literature review. The study integrates analytical tools such as SWOT, Value Chain, Porter’s Five Forces, PEST, and McFarlan’s Strategic Grid to evaluate internal and external environments. Findings reveal strengths in operational efficiency and customer engagement, alongside challenges like reliance on manual reservation systems and limited product diversification. Based on these insights, a strategic IS application portfolio and phased implementation plan were proposed to align IT investments with strategic objectives. The proposed solutions are expected to improve reservation handling, enhance customer engagement, and increase operational efficiency. This study highlights the innovative application of the Ward and Peppard methodology in the recreational sports industry, offering a scalable framework for other businesses to address similar operational challenges. Future research could extend this approach to real-world implementations or explore its adaptability across diverse sectors.